DETERMINATION OF PUMICE PYROCLASTIC DENSITY OF RINJANI MOUNTAIN ERUPTION AND ITS SPREADING SIMULATION USING HAZMAP SOFTWARE - Wardani, Aulia Fatma; Al Hadi, Kasnawi; Qomariyah, Nurul; Minardi, Suhayat (Universitas Mataram, 2019)
Volcano represent channel of systems fluid (lava), which has a depth up to 10 km from the earth surface. One ofthe active volcanoes is Mount Rinjani which recorded the eruption was 9 times from 1846 to 1994. The result ofthe eruption of Mount Rinjani is pyroclastic rocks dominated by pumice, which accumulated at lot of areas ofresearch that will be determined by the density value calculation method. The resulting rock density values canbe used to see the spread of the volcanic eruption material with simulation software based on data Hazmaperuption in 1994. The result of this research is the density of pumice and simulated the spread of the eruption ofMount Rinjani 1994. The density of pumice is about 693 kg/m3 and deployment simulation shows the distributionof the eruption of Rinjani to the diameter size of the fine dust (<1/16 mm) spread towards the Northwest (NorthLombok) with total mass about 6,38x109 kg and diameter size of lapilli (2-10) mm spread around the center ofthe eruption (Mount Rinjani) with total mass about 5, 16x109 kg.